Fibrin Glue Enhances Adipose-Derived Stromal Cell Cytokine Secretion and Survival Conferring Accelerated Diabetic Wound Healing - Ursula Hopfner; Matthias M. Aitzetmueller; Philipp Neßbach; Michael S. Hu; Hans-Guenther Machens; Zeshaan N. Maan; Dominik Duscher (Stem Cells International)
Introduction. Although chronic wounds are a major personal and economic burden, treatment options are still limited. Among those options, adipose-derived stromal cell- (ASC-) based therapies rank as a promising approach but are restricted by the harsh wound environment. Here we use a commercially available fibrin glue to provide a deliverable niche for ASCs in chronic wounds. Material and Methods. To investigate the in vitro effect of fibrin glue, cultivation experiments were performed and key cytokines for regeneration were quantified. By using an established murine chronic diabetic wound-healing model, we evaluated the influence of fibrin glue spray seeding on cell survival (In Vivo Imaging System, IVIS), wound healing (wound closure kinetics), and neovascularization of healed wounds (CD31 immunohistochemistry). Results. Fibrin glue seeding leads to a significantly enhanced secretion of key cytokines (SDF-1, bFGF, and MMP-2) of human ASCs in vitro. IVIS imaging showed a significantly prolonged murine ASC survival in diabetic wounds and significantly accelerated complete wound closure in the fibrin glue seeded group. CD31 immunohistochemistry revealed significantly more neovascularization in healed wounds treated with ASCs spray seeded in fibrin glue vs. ASC injected into the wound bed. Conclusion. Although several vehicles have shown to successfully act as cell carrier systems in preclinical trials, regulatory issues have prohibited clinical usage for chronic wounds. By demonstrating the ability of fibrin glue to act as a carrier vehicle for ASCs, while simultaneously enhancing cellular regenerative function and viability, this study is a proponent of clinical translation for ASC-based therapies.